The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1159/000345477
|View full text |Cite
|
Sign up to set email alerts
|

Think Global – Act Local: Intravitreal Drug Delivery Systems in Chronic Noninfectious Uveitis

Abstract: The eye is probably the most attractive site of the body for treatment using locally delivered therapeutic agents. An ideal indication for such an approach is noninfectious posterior uveitis. Since intraocular structures of the posterior segment are difficult to reach and are otherwise accessible only by systemic treatment, current interest is focused on the pros and cons of intravitreal drug delivery. Because of its chronic and recurrent nature, the long-term release of anti-inflammatory agents is a major tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 87 publications
0
14
0
1
Order By: Relevance
“…For example, antibacterial therapy typically requires sustained local concentrations for periods of days to weeks, whereas some diseases, such as tuberculosis, necessitate daily doses of antibiotics for at least 6 mo (1). Other diseases also have demonstrated benefits from a long-term multimonth drug regimen, including cystic fibrosis (2), ankylosing spondylitis (3), and chronic uveitis (4).…”
mentioning
confidence: 99%
“…For example, antibacterial therapy typically requires sustained local concentrations for periods of days to weeks, whereas some diseases, such as tuberculosis, necessitate daily doses of antibiotics for at least 6 mo (1). Other diseases also have demonstrated benefits from a long-term multimonth drug regimen, including cystic fibrosis (2), ankylosing spondylitis (3), and chronic uveitis (4).…”
mentioning
confidence: 99%
“…It releases active drug at a rate of 0.3-0.4 mcg/day over a period of *2.5 years. [14][15][16] Several studies have demonstrated its efficacy in reducing recurrence, improving vision, better control of inflammation compared to systemic therapy, and reducing the need for systemic immunosuppressive medication in noninfectious posterior uveitis and panuveitis. [16][17][18][19] A randomized, controlled, phase II/III trial demonstrated a lower rate of recurrence of uveitis in Retisertimplanted eyes (18.2%) compared with those receiving systemic corticosteroids (63.5%).…”
Section: Intraocular/intravitreal Implantsmentioning
confidence: 99%
“…The first of these Mini Reviews will be found in this volume of Ophthalmic Research [1]. We start with a topic that has been a focus of the journal for several years: intravitreal drug delivery.…”
Section: Focus On: Intravitreal Therapy In Noninfectious Uveitismentioning
confidence: 99%